2002
DOI: 10.1007/s003920200034
|View full text |Cite
|
Sign up to set email alerts
|

Körperliches Training als Intervall- oder kontinuierliches Training bei chronischer Herzinsuffizienz zur Verbesserung der funktionellen Leistungskapazität, Hämodynamik und Lebensqualität – eine kontrollierte Studie

Abstract: We conducted a three-week randomized trial comparing the improvement of functional capacity by exercise training in chronic heart failure by the steady-state (EF 27.3%, n = 20) and the interval modus (EF 29.3%, n = 20) with a control group (EF = 26.6%, n = 10). Minimal EF was 10%, the lowest maximal oxygen consumption was 9.3 ml/kg/min and the lowest cardiac output was 1.9 l/min; 9 patients had been evaluated for HTX. VO2 at the anaerobic threshold and at maximal exercise increased in the continuous exercise g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Taken together, studies performed in HFREF patients suggest that the increased peak VO 2 after 2 to 6 months of endurance exercise training is due to increased peak CO and/or A-VO 2 Diff. When present, increased peak CO was due primarily to increased peak heart rate as peak stroke volume was not significantly increased after training in any of these studies in HFREF patients 16, 17, 19-21, 40, 41 .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Taken together, studies performed in HFREF patients suggest that the increased peak VO 2 after 2 to 6 months of endurance exercise training is due to increased peak CO and/or A-VO 2 Diff. When present, increased peak CO was due primarily to increased peak heart rate as peak stroke volume was not significantly increased after training in any of these studies in HFREF patients 16, 17, 19-21, 40, 41 .…”
Section: Discussionmentioning
confidence: 57%
“…In HFREF patients, Hambrecht et al 19, 22 reported that 6 months of endurance exercise training increased peak exercise heart rate and CO. In contrast, Sullivan et al 16 and others 17, 39, 40 reported no significant change in peak stroke volume and CO after endurance exercise training in HFREF patients, and that increased peak A-VO 2 Diff measured invasively by direct oximetry was the major contributor to improved exercise capacity. Dubach et al 21 found that 2 months of high-intensity endurance training improved both peak exercise CO and A-VO 2 Diff in HFREF patients.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Wisloff et al (2007) reported that high-intensity interval aerobic training was superior to continuous moderate intensity endurance exercise training for improving resting LV ejection fraction, peripheral vascular function, and skeletal muscle mitochondrial biogenesis in elderly men with HFREF. Nechwatal et al (2002) found that short-term high-intensity aerobic interval training significantly increased peak exercise stroke volume and CO and reduced systemic vascular resistance but there was no change in these outcomes after moderate intensity continuous endurance training in patients with HFREF.…”
Section: Exercise In Elderly Patients With Heart Failure and Reduced mentioning
confidence: 99%
“…In addition, several previous studies had reported that interval training at a relatively higher intensity could be used in both clinical practice and experiments, and that such exercise modality had greater beneficial effects on the heart 8,9 . Those characteristics suggest that intermittent training can be more appropriate to individuals with metabolic syndrome, dyslipidemia and other cardiovascular risk factors 10-12 . However, little is known about the acute and subacute differences obtained with that exercise modality as compared to traditional continuous training.…”
Section: Introductionmentioning
confidence: 99%